Violência praticada por mulheres: o impacto dos discursos dominantes em narrativas científicas, virtuais e individuais no Brasil - Carvalho, Tácio Sales (2023)
Monological discourses about human violence have structured subjectivities, established power relations and impacted social practices, creating the false idea that "women are not violent" or "are less violent than men". In this context, the aim of this research is to understand the meanings of violence practiced by women in Brazil, based on scientific, virtual and individual narratives. The research was carried out from the meta-theoretical perspective of social constructionism and using a mixed research method. In the quantitative phase, the data was analyzed using the statistical software qualtrics comentto and atlas.ti. In the qualitative phase, the content was interpreted using the notion of constructing meanings. The results are presented in three chapters. The first, developed through an integrative literature review, indicates that the meanings of psychology's scientific narratives on the subject have been hegemonically constructed based on epistemic silence. The second, developed through online ethnography, points out that the meanings of virtual narratives on the internet have been constructed on the basis of questioning, preserving and indicating the negative repercussions of dominant discourses on social relations. The third, produced through the application of survey questionnaires and semi-structured interviews, points out that the meanings of the individual narratives of professionals have been built on the feminization of discourses on violence, on universal essentialist notions about women and on the contemporary contradictions experienced in social relations. The research proposes a coparticipatory process between men and women in professional practice and scientific production on human violence, with a view to overcoming injustice, inequality, sexism, scientific racism and discursive bias